PENGARUH SIKAP BELAJAR DAN FASILITAS PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI: (Survei terhadap siswa kelas XI IPS Mata Pelajaran Ekonomi di SMAN 1 Cineam Tahun Ajaran 2023/2024) - Ratna Nurrahmawati; Heti Suherti; Raden Roro Suci Nurdianti (JOURNAL SAINS STUDENT RESEARCH, 2024)
Abstact. The problem in this research is the low learning outcomes seen from the less than optimal final semester exam scores. This research aims to determine the influence of learning attitudes and learning facilities on learning outcomes. The research method used in this research uses a survey method with an explanatory design. The population in this study was class XI IPS students at SMAN 1 Cineam with a total of 91 people. The sampling technique used was a saturated sample with a sample size of 91 respondents. Based on the research results, 1) there is a significant influence between learning attitudes on student learning outcomes with (4,551 > 1,987). 2) there is a positive and significant influence on learning facilities on learning outcomes ( 12,347 > 1,987). 3) there is a positive and significant influence on learning attitudes and learning facilities on student learning outcomes with ( 168,918 > 3,10). The conclusion of this research is that learning attitudes and learning facilities have a positive and significant effect on student learning outcomes. Suggestions from researchers are that teachers or educators are expected to better supervise and guide students who still have a learning attitude and are responsive in reporting to the deputy head of facilities and infrastructure when there are damaged learning facilities. This is because the learning process is carried out more effectively and efficiently. Students are expected to be able to improve their learning outcomes, namely by having a good learning attitude and utilizing existing facilities at school to increase their knowledge, especially in economic subjects. This is to obtain optimal learning results.